Comparison and Benchmarking of NMPC for Swing-Up and Side-Stepping of an Inverted Pendulum with Underlying Velocity Control. Issue 14 (2021) - Husmann, Ricus; Aschemann, Harald
Abstract: This paper presents the design and investigation of a nonlinear model predictive controller (NMPC) for an inverted pendulum with velocity input. The controller is implemented on a test-rig using the GRAMPC-Toolbox. It is shown that swing-up/ stabilisation and side-stepping can be achieved in a single controller using a suitable cost functional as well as prediction horizon. The impact of different NMPC design parameters on the achievable performance and stability properties is investigated and discussed. Finally, a comparative analysis with an alternative nonlinear control – consisting of energy-based swing-up and a tracking controller based on extended linearisation techniques and state-dependent Riccati equations (SDRE) – is carried out. The individual strength or weakness is discussed based on experimental results at a test rig.